Gestos de subjetivação: as dificuldades para realizar uma história do corpo e da sexualidade - Santos, Fausi dos; Momesso, Maria Regina; Ribeiro, Paulo Rennes Marçal [UNESP] (My University, 2014)
The article presents, from the Analysis of French Discourse, different gestures of reading and interpretation of the body and sexuality at various times in history. It demonstrates that such gestures reading are the fruit of experience that each society sets about their cultural values and norms in each period, both in the first civilizations to the economy of sex for birth control and the survival of the group and in the Medieval Christianity control of sex in the fight against sin. Each society according to Michel Foucault, establishes a system of knowledge and power to order and classify the type of body and citizen you desire, like the city of Sparta with its regime of knowledge and training of the soldier and in Athens with the democratic regime in the formation of the political, or contemporary society in the formation of the body of perfect proportions that meet the stipulations of the market.

O artigo apresenta, a partir da Análise do Discurso de linha francesa, diferentes gestos de leitura e interpretação sobre o corpo e a sexualidade em variados momentos da história. Demonstra que tais gestos de leitura são frutos da experiência que cada sociedade estabelece sobre os seus valores e normas culturais em cada época, seja nas primeiras civilizações com a economia do sexo para o controle da natalidade e a sobrevivência do grupo ou o cristianismo medieval no controle do sexo na luta contra o pecado. Cada sociedade, segundo Michel Foucault, estabelece um regime de saberes e poderes que ordenam e classificam o tipo de corpo e cidadão que deseja, foi assim na cidade guerreira de Esparta com seu regime de saberes na formação do soldado ou em Atenas com o regime democrático na formação do político ou ainda na sociedade contemporânea, na formação do corpo de proporções perfeitas que atendam as determinações do mercado.
Keywords: Body; Sexuality; Power; Society; Corpo; Sexualidade; Poder; Sociedade